Stress-induced vulnerability to develop cocaine addiction depends on cofilin modulation - Rigoni, Daiana (2021)
Actin dynamics in dendritic spines can be associated with the neurobiological mechanisms supporting the comorbidity between stress exposure and cocaine increase rewards. The actin cytoskeleton remodeling in the nucleus accumbens (NA) has been implicated in the expression of stress-induced cross-sensitization with cocaine. The present study evaluates the involvement of cofilin, a direct regulator of actin dynamics, in the impact of stress on vulnerability to cocaine addiction. We assess whether the neurobiological mechanisms that modulate repeated-cocaine administration also occur in a chronic restraint stress-induced cocaine self-administration model. We also determine if chronic stress induces alterations in dendritic spines through dysregulation of cofilin activity in the NA core. Here, we show that the inhibition of cofilin expression in the NA core using viral short-hairpin RNA is sufficient to prevent the cocaine sensitization induced by chronic stress. The reduced cofilin levels also impede a-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor surface expression enhancement and promote the reduction of head diameter in animals pre-exposed to stress after a cocaine challenge in the NA core. Moreover, downregulation of cofilin expression prevents facilitation of the acquisition of cocaine self-administration (SA) in male rats pre-exposed to chronic stress without modifying performance in sucrose SA. These findings reveal a novel, crucial role for cofilin in the neurobiological mechanisms underpinning the comorbidity between stress exposure and addiction-related disorders.